Assessment of farmers’ readiness to face challenges of the post-Movement Control Order (MCO) in the central zone of Malaysia - Arif Shah, Jasmin; Mazlan, Nur Izzatie; Mohamed Haris, Nur Bahiah (Human Resource Management Academic Research Society, 2022)
Farmers' readiness to manage agricultural issues determines their capacity to anticipate, prevent, and adapt to upcoming threats and shocks. Farmers’ readiness to face challenges by the Movement Control Order (MCO) causes the new challenges faced by the agricultural community. On the 18th March 2020, the Malaysian government implemented the MCO to control the spread of COVID-19 pandemic cases in Malaysia. Restriction of movement affected the agricultural sectors as farmers were unable to manage their farms and sell their products routinely. There is miscommunication between farmers and distributor where all agriculture transportation activities ceased during MCO, thus affect the dump of excess of vegetables. Farmers face various obstacles to crop diversification, such as lack of capital, lack of support, marketing problem, and production risks. Thus, this study aimed to determine the factors that influenced farmers’ readiness to face challenges post-MCO phase within the central zone of Malaysia. The study used quantitative procedures. The study employed a simple random sampling method and utilized a survey methodology consisting of six sections of questions. A total of 85 vegetable farmers were selected as respondents. The data for this study was collected through two methods, namely online data collection via Google Form and manual data collection via face-to-face approach. The findings indicated that technology, implementation, leadership, and decision-making skills significantly show a moderate to a high level of farmers’ readiness to face challenges post-MCO. The highest factor contributing to farmers’ readiness is decision-making skill. The adjusted R2 value of 0.533 implies that the decision-making skill explains about 53% of the variance in the farmer’s readiness in this study. Hence, this shows that decision-making skills was the major empirical findings can lead to farmers' empowerment and readiness to face challenges post-MCO. This study points out that there is a need to address the research on information and communication technology (ICT) factors that influence the farmers’ readiness to face risk to empower and boost agricultural productivity.